2016
DOI: 10.1111/jar.12287
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Special Olympics Experiences from the Athlete Perspectives Using Photo‐Elicitation: A Qualitative Study

Abstract: Photo-elicitation was a useful and important tool in assisting athlete participants to communicate their motivations to participate in sport in ways that using traditional verbal interviewing would not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 58 publications
(106 reference statements)
4
33
0
Order By: Relevance
“…These findings are supported by previous research on athletes with ID and their motives for participating in sport who identified a combination of intrinsic and extrinsic motivational factors as influencers (Farrell et al, 2004; Harada & Siperstein, 2009; Shapiro, 2003). They are also consistent with previous qualitative studies that found fun and social connections as important motivators for athletes to continue their participation in sport, allowing them to experience an improved quality of life and increased abilities (Mason, Timms, Hayburn, & Watters, 2013; Weiss et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings are supported by previous research on athletes with ID and their motives for participating in sport who identified a combination of intrinsic and extrinsic motivational factors as influencers (Farrell et al, 2004; Harada & Siperstein, 2009; Shapiro, 2003). They are also consistent with previous qualitative studies that found fun and social connections as important motivators for athletes to continue their participation in sport, allowing them to experience an improved quality of life and increased abilities (Mason, Timms, Hayburn, & Watters, 2013; Weiss et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…They felt they would benefit from greater choices in training offered by their coaches and further opportunities to provide input relating to their own sporting involvement and progression. Interestingly, similar findings were presented by another qualitative study that dealt not only with what SO athletes tend to like and perceive helpful based on their participation (Robinson et al, 2018; Weiss et al, 2017) but also which elements of their training that athletes usually find detrimental for their sporting participation (Farrell et al, 2004). It is important to note, therefore, that these factors may be barriers to participation for athletes (and nonathletes) with ID and may be reasons for athletes to choose to terminate their sporting endeavours with the SO.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Farrell, Crocker, McDonough and Sedgwick (2004) interviewed 38 adult SO athletes and noted that athletes seek out experiences of competence, autonomy and relatedness, while Harada and Siperstein (2009) interviewed adult SO athletes and their families and found that enjoyment, happiness, friendship and achievement were common reasons for participation. A more recent photo‐elicitation study of five SO athletes (ages 13 to 33) identified themes of connectedness (with friends, teammates and coaches) and training in sport (dedication to sport, competition and trophies) as being central to athlete perceptions of why sport matters to them (Weiss et al ., 2017). Further, qualitative research with parents of young athletes in SO suggests parents believe SO offers an instructional environment that fosters personal competence, instils a sense of self‐efficacy, encourages athletes to set and work towards physical and social goals and is a secure and accepting environment that fosters relatedness and happiness (Goodwin, Fitzpatrick, Thurmeier, & Hall, 2006).…”
mentioning
confidence: 99%